Pendaftaran Akta Wasiat Ke Pusat Daftar Wasiat oleh Notaris di Kota Padang - Devia Rahma Pratisa; Azmi Fendri; Syofiarti Syofiarti (UNES Law Review, 2023)
Registration of a will at the will registration center by an online notary in the city of Padang is a notary's obligation as regulated in article 16 paragraph 1 letter j UUJN, whether there is a will or not, a notary is still obliged to register the will within the first 5 (five) days of every week. the following month, as for notaries in the city of Padang who do not register a register of wills or a register of zero wills caused by the notary's negligence, this can cause losses to third parties or heirs, besides that the notary has also been deemed negligent in his obligations as regulated in the UUJN. This study proposes a formulation of the problem, namely: 1. What is the urgency of registering a will at the center of the testament register by a notary in the city of Padang? 2. How is the practice of registering a will at the center of the register of wills by a notary in the city of Padang? 3. How is the supervision of the notary's obligation to register a will at the testament register center in the city of Padang? This study uses a juridical-empirical approach.The research results show that: 1. The urgency of registering a will deed is apart from the notary's obligations in article 16 paragraph 1 letter j UUJN, registration of a will is very important because if the will deed is not registered, the notary in his SKW will not be able to calculate the distribution of the heirs, the notary will experience difficulties when making the APHW so that the recipient of the will will experience difficulties in obtaining inheritance rights, therefore the inheritance returns to ab intestate inheritance so that the recipient of the will in the SKW cannot be named 2. The process of implementing will registration according to several notaries in the city of Padang is in accordance with applicable laws and regulations, namely Ministry of Law and Human Rights Regulation No. 60 of 2016 concerning Procedures for Reporting Wills and Applications for Electronic Issuance of Will Certificates.The notary no longer sends a physical list manually as proof of a report regarding a will that has been made, the notary only needs to register to be able to enter the Director General of AHU's website and send a report regarding the will online 3. In carrying out supervision the MPD conducts an examination on the basis evaluation is then carried out coaching, during the examination if the person concerned (notary) still violates it then the MPD makes a recommendation to the MPW to be followed up on.